One Snowy Night - Butler, M. Christina; Macnaughton, Tina (Intercourse, PA : Good Books, 2020)
Awakened from hibernation when an ill-fitting, gift-wrapped red wool cap falls nearby, Little Hedgehog passes along the present to Rabbit, but somehow ends up with it again by the end of the day.
Cover title.
On board pages.
"A touch-and-feel book"--Cover.
"Original edition published by Good Books in 2004" -- P. [4] of cover.
"Original edition published in English by Little Tiger Press, an imprint of Magi Publications, London, England, 2004"- -P. [4] of cover.
new kids book spring 2024.
Keywords: Hedgehogs -- Juvenile fiction; Animals -- Juvenile fiction; Hats -- Juvenile fiction; Toy and movable books; Textured books; Christmas stories (Juvenile); Board books; Picture books